Factors Affecting Attitude towards Online Music Piracy and Willingness to Try Subscription-Based Music Services (SBMS)? - Adhika Putra Wicaksono; Erna Andajani (Journal of Economics, Business, and Accountancy Ventura, 2023)
Currently, subscription-based music services (SBMS) are one of the legal channels for listening to music and a viable alternative to reduce digital music piracy. SBMS is one of the complementary channels for digital music piracy because it allows users to sample music (legally) and then download it illegally. This research aimed to analyze individual attitudes and intentions towards digital music piracy and willingness to try SBMS by considering the religiousness variable. This study used the non-probability sampling technique, analyzed 200 questionnaires, and processed them using structural equation modeling (SEM). The results of this study stated that the attitude towards digital piracy was positively influenced by economic benefit, hedonic benefit, and extrinsic religiousness and negatively influenced by moral judgment, while willingness to try SBMS was positively influenced by involvement. This paper provides more empirical evidence regarding the impact of religiousness on attitudes toward digital piracy and willingness to try SBMS. This research has made a significant contribution and shows the anomaly that although Indonesia is a religious country, it has a high rate of digital piracy. This study suggests the need for commitment and cooperation between governments, streaming music service providers, and musicians to educate Indonesians about the consequences and implications of digital music piracy.